Feminist Critical Discourse Analysis on the Multimodal Means in Beauty Product Advertising in Vogue Magazine - Sakko, Eveliina (My University, 2024)
This thesis examines the multimodal means used in beauty product advertisements that were published in the women’s magazine Vogue. A total of 20 advertisements for different skincare and makeup products from six cosmetics brands were analyzed for this study, and the advertisements were accessed through the Vogue Archive. The theoretical framework of this study comes from visual grammar that was introduced by Gunther Kress and Theo van Leeuwen in Reading Images: The Grammar of Visual Design (2006), as well as from feminist critical discourse analysis, or FCDA. The research questions were as follows: 1. What kind of multimodal means introduced in Kress and van Leeuwen’s visual grammar were used in the advertisements and why? 2. From the point of view of feminist critical discourse analysis, how are the multimodal means connected to possible power imbalance in society or the disempowerment of women? The results of the analysis show that many of the concepts from visual grammar can be found in cosmetics advertising, and especially power and authority are highlighted through visual choices related to, for instance composition and angles. The language in the advertisements often emphasizes different issues people may have with their appearance, and they make use of imperatives and personal language to persuade consumers. In the context of FCDA, cosmetics advertising can create even harmful and unrealistic ideals for women, and in turn affect the power imbalances that exist in society.
Keywords: advertising, advertising language, cosmetics, FCDA, multimodality, visual grammar